Hubungan Kondisi Overcrowded dengan Ketepatan Pelaksanaan Triase di Instalasi Gawat Darurat - Faradilla Miftah Suranata (Universitas Muhammadiyah Manado, 2023)
Intoduction Triage is a process of sorting patients based on the severity and the mildness of trauma or illness suffered. This triage process must be carried out immediately and in a short time. In addition, the implementation given in handling emergency cases must be appropriate, because inaccuracy in decision making will cause adverse effects such as treatment delay and disability in patients. The purpose of this research was to find out the corellation between overcrowded conditions with the accuracy of triage implementation in the Emergency Room of the DTIU of Type C Manembo-nemboRegional Hospital in Bitung. Research Design This research was conducted by using a descriptive analytic method with a cross sectional design. Sampelswere taken based on the number of respondents as many as 32 people using total sampling technique. Data collection was done by doing observation. Then, the collected data was processed by running the SPSS computer program version 16.0 to be analyzed by aFisher Exact test with the significance level α = 0,05. The result showed that the accuracy of the triage implementation correctly amounted to 18 respondents (56,2 %) dan which is not correct there are 14 respondents (43,8%). From the Chi Square test, it was obtained the ρ value = 0,001< α = 0,05. Conclusion The conclusion of this research is that there is acorellation between overcrowded conditions with the accuracy of triage implementation in the Emergency Room of the DTIU of Type CManembo-nemboRegional Hospital in Bitung. It is suggested to nurses to be able to take appropriate action in the implementation of triage with overcrowded conditions in order to reduce morbidity and mortality in hospitals.